Zirconium in the Nuclear Industry: Twelfth International Symposium 2000
DOI: 10.1520/stp14297s
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Dislocation and Precipitate Structure in Zr Alloys Under Long-Term Irradiation

Abstract: Tubes from zirconium-base alloys are used widely in the pressure tube reactor core. The lifetime of the zirconium component in the reactor core will be determined by structure changes and alloy properties under long-term neutron irradiation. The studies were carried out using Zr-1Sn-1Nb-0.4Fe (E635) and Zr-2.5Nb (E125) alloy samples cut out of a pressure tube (PT) in the initial condition and after 7 and 15.5 years operated (42 000 and 95 000 effective hours) under irradiation to the neutron fluxes of 3 × 1017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 7 publications
3
12
0
Order By: Relevance
“…Interestingly, the authors observed no β-Nb phases within α-Zr when the alloy Nb content is 0.29 wt.% and did observe β-Nb when the Nb content was 0.49 wt.%. This leads to the conclusion that Nb TSS in α-Zr is in the range 0.29-0.49 wt.% at temperatures below the Zr-Nb monotectoid temperature (<600 °C), a value much greater than that suggested by Canay et al Figure 1 Ternary Zr-Nb-Fe diagram generated from data after [3,[20][21][22][23][24][25][26][27]29,[41][42][43][44]46,[62][63][64]. All compositions are given in at.%.…”
Section: Nb Terminal Solid Solubility In α-Zrmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the authors observed no β-Nb phases within α-Zr when the alloy Nb content is 0.29 wt.% and did observe β-Nb when the Nb content was 0.49 wt.%. This leads to the conclusion that Nb TSS in α-Zr is in the range 0.29-0.49 wt.% at temperatures below the Zr-Nb monotectoid temperature (<600 °C), a value much greater than that suggested by Canay et al Figure 1 Ternary Zr-Nb-Fe diagram generated from data after [3,[20][21][22][23][24][25][26][27]29,[41][42][43][44]46,[62][63][64]. All compositions are given in at.%.…”
Section: Nb Terminal Solid Solubility In α-Zrmentioning
confidence: 99%
“…The Fe and Nb is enriched in the metastable phase states, and forms discrete ZrNbFe precipitates in advance of the complete decomposition of the β-Zr phase to β-Nb [10]. The compositional range for β-Nb is given from several studies in the ternary diagram of Figure 1 using data from [20][21][22][23][24][25][26], an analysis of which is shown in Figure 2. The diagram in Figure 1 represents the phases identified at room temperature, some of which may not be equilibrium phases.…”
Section: The β-Nb Phase and "Where The Iron Goes"mentioning
confidence: 99%
See 1 more Smart Citation
“…This is approximately a factor of 10 higher than the expected number densities of <a>-type dislocation loops after a similar neutron irradiation dose. The build-up of layers of particles resembles the arrangement of <a>-loops seen with TEM [2,[21][22][23][24] and it is therefore possible -but not certain -that there is some correlation between the clustering and such defects. In particular there is agreement between the size and number densities of clusters and the small prismatic loops that were observed in Zircaloy-2 by Idrees [24].…”
Section: Cr Distributionmentioning
confidence: 99%
“…The Zr(Fe,Cr) 2 precipitates can already exhibit the hexagonal and the face centred cubic structure, being both close packed structures. The ZrCr 2 , Zr(Fe,V) 2 [31] and Zr(Fe,Nb) 2 [33,34] exhibiting delayed oxidation all have either the hexagonal or the face centred cubic structure.…”
Section: Precipitate Sizementioning
confidence: 99%